Akibat Hukum Penerbitan Hak Guna Bangunan Di Atas Laut Dakam Perspektif Hukum Agraria Dan Tata Ruang - Yusuf Margo Prihandoyo (JUSTNESS - Jurnal Hukun Politik dan Agama, 2025)
The issuance of Building Use Rights (HGB) over marine areas has become a legal polemic in Indonesia because it contradicts the Basic Agrarian Law, which explicitly stipulates that the object of HGB is land. This study aims to examine the legal validity of the issuance of HGB over the sea and its resulting legal consequences, using normative legal methods with a conceptual and statutory approach. This study shows that the issuance of HGB over the sea constitutes a form of legal deviation because the sea is not included as an object of land rights. This action creates legal uncertainty, overlapping regulations between the Basic Agrarian Law and sectoral laws such as Law No. 32 of 2014 concerning Maritime Affairs and Law No. 1 of 2014 concerning the Management of Coastal Areas and Small Islands, and negatively impacts coastal community access and marine environmental sustainability. The case of the issuance of HGB in Kohod Village is a clear example of weak inter-agency coordination and legal loopholes exploited by certain individuals. The issuance of HGB is only valid if it is carried out on reclaimed land that has been designated as state land. Therefore, harmonization of regulations between agrarian and maritime law, strengthening oversight, law enforcement, and protecting the rights of coastal communities are needed. This study contributes to reforming Indonesia's land law system to align it with the principles of justice, legal certainty, and sustainable development, particularly in the context of managing marine and coastal areas, which are increasingly strategic in the era of future spatial utilization.